2021
DOI: 10.1186/s40462-020-00238-2
|View full text |Cite
|
Sign up to set email alerts
|

Bats seek refuge in cluttered environment when exposed to white and red lights at night

Abstract: Background Artificial light at night is recognized as an increasing threat to biodiversity. However, information on the way highly mobile taxa such as bats spatially respond to light is limited. Following the hypothesis of a behavioural adaptation to the perceived risks of predation, we hypothesised that bats should avoid lit areas by shifting their flight route to less exposed conditions. Methods Using 3D acoustic localization at four experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
3
28
0
4
Order By: Relevance
“…Among bats, species composing regional communities often respond in different ways, with both spectral composition and intensity influencing response; few patterns of bat response to ALAN apply to all species [ 80 , 81 ]. In general, experiments consistently demonstrate certain species of bats avoiding experimentally lit areas of landscapes, whereas other species in a local bat community might forage opportunistically on insects at the lights [ 82 , 83 ]. For example, experimental treatment with ALAN reduced drinking by forest bats in Italy [ 84 ], and in an urban area of Germany, greater noctule bats ( Nyctalus noctula ) tended to avoid lit areas but opportunistically foraged in some situations [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among bats, species composing regional communities often respond in different ways, with both spectral composition and intensity influencing response; few patterns of bat response to ALAN apply to all species [ 80 , 81 ]. In general, experiments consistently demonstrate certain species of bats avoiding experimentally lit areas of landscapes, whereas other species in a local bat community might forage opportunistically on insects at the lights [ 82 , 83 ]. For example, experimental treatment with ALAN reduced drinking by forest bats in Italy [ 84 ], and in an urban area of Germany, greater noctule bats ( Nyctalus noctula ) tended to avoid lit areas but opportunistically foraged in some situations [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, human populations in major cities in South Africa are projected to increase by as much as 23% by 2030 [ 62 ]. Urbanisation generally impacts bat populations negatively through habitat loss, artificial lights (through insect prey loss and commuting disruption) and vehicle collisions on major roads [ 10 , 49 , 72 ]. Both M. natalensis and R. aegyptiacus appear to be adaptable foragers in urban settings [ 8 , 79 ], yet little evidence is available as to how these species respond to areas that have recently undergone land-use transformation .…”
Section: Discussionmentioning
confidence: 99%
“…Gaston et al, (2012) suggested five levers to reduce light pollution: prevent dark areas from being lit, limit the duration of artificial lighting, reduce light trespass, reduce light intensity and change ALAN spectral composition. Bats are known to present different responses to light with different spectra (Barré et al, 2021;Lewanzik & Voigt, 2017;Spoelstra et al, 2017;Straka et al, 2020). However, in this study, we could not assess how different spectral compositions would have affected our results, as the light pollution data available at landscape scale were not made of multiple spectral bands.…”
Section: 3management Consequencesmentioning
confidence: 94%